Investigating the potential of South African Entomopathogenic nematodes for the management of Ceratitis capitata (Wiedemann) - Wimbush, Richard Dillon (Stellenbosch : Stellenbosch University, 2026)
Thesis (MScAgric)--Stellenbosch University, 2026.